Analisis Strategi Guru Dalam Mengembangkan Karakter Berpikir Kritis Siswa Kelas Tinggi SDN Sawojajar 01 - Yeni Aenun Firdah; Diah Sunarsih; Moh. Toharudin (Concept: Journal of Social Humanities and Education, 2023)
Based on the problem background, the researcher conducted research on developing critical thinking in high school. Which is where this study aims to describe teacher strategies in developing critical thinking characters in high grades. This study uses a type of qualitative research. The research location was at SD Negeri Sawojajar 01. The implementation of this research was in June 2023. Respondents in this study were class IV teachers, class V teachers, class IV students and class V students. Data collection techniques used interviews, observation, and documentation. Data validity was carried out by source triangulation and technique triangulation. Data analysis techniques used are data collection, data reduction, data presentation and conclusion. The result of this research is to develop critical thinking in high grades, one of which is SD Negeri Sawojajar 01. The teacher's strategy in developing the critical thinking character of high grade students at SDN Sawojajar 01. Learning at school can be done in the classroom. From the results of this study students produce effective learning so that it will help teachers more easily do learning in class. Because students in high grades have thoughts that are conducive to learning.